Sistem takaful di Malaysia : isu-isu kontemporari - Asmak Ab. Rahman; Penerbit Universiti Malaya (Kuala Lumpur: Penerbit Universiti Malaya, 2008)
Islamic aspect of insurance in Malaysia.
Includes bibliographical references (p. [169]-179) and index.
Keywords: Insurance -- -- Malaysia; Insurance -- -- Religious aspects -- -- Islam